Bank lending to new and growing enterprises - Churchill, Neil C.; Lewis, Virginia L. (Journal of Business Venturing, 1986)
This paper confirms and expands on an earlier study (Churchill and Lewis 1985) into the profitability of bank lending to small businesses—those under $50 million in sales. The earlier study found that bank lending to small companies was more costly than lending to large corporations due primarily to administrative costs and risk that were higher (per dollar of loan) than the interest differential charged. It found, however, that the larger deposit balances left with the bank not only offset these costs but made lending to small firms 2.76 percentage points more profitable. This suggested that small businesses should be able to continue to borrow from large banks in spite of the consolidation now taking place in the banking industry. The research reported upon here addresses the issue left open by the initial study, that possible different lending policies and account profitability exist for different size companies under $50 million in sales. This issue was examined by looking at 116 individual account relationships representing both large and small borrowers. Taken as a group, the bank relationships of these companies are comparable to those in the original study—the return to the bank on it assets (loans outstanding)-for companies under $50 million was much higher, 3.34% versus 1.94% for larger companies; the amount of deposits left by the borrower with the bank was 43% of loan dollars for the smaller companies versus 9% for the larger ones: and the “risk class” assigned by the bank was essentially the same. When comparisons were drawn by size for companies under $50 million in sales—the main purpose of this study-many similarities, and only a few differences, were obtained. These were, for the six size categories from “under $500,000” to “$25 million and over,” as follows: •• First, and most importantly, loan relationships were profitable for small companies of all sizes and, for all but those in the smallest category, more profitable than loan relationships with large companies.•• Second, and of almost equal importance, essentially no differences that are significant to managers were found as between companies of different size. The most important of differences were found as follows: ◦• Perceived risk to the bank (assigned risk class) of loans to companies in the largest category (over $25 million) was lower than for all others, and was greater for companies in the $1 million to $2.9 million category. Non-performing loan data provided some foundation for this.◦• Deposits with the bank were lowest for companies in the smallest category, increased with size until the largest category was encountered, and then dropped off.On the whole, the study paints a very encouraging picture for the future availability of credit to small and growing businesses: •• Except for very young businesses (primarily those just starting out) banks treat small companies in a rather even-handed manner and do no seem to discriminate with respect to size.•• Bank relationships with small companies of any size are, in general, more profitable than relationships with large companies.•• Deposits kept by small businesses are the key to this greater profitability, but losses and administrative expenses do not seem to be unduly burdensome. The major messages emerging from these studies are: •• Banks can view small businesses as a very attractive source of profit.•• The owner-manager can continue to receive bank financing as long as profit continues to be a motivator for banks.•• The relationship between bankers and entrepreneurs need to be adversarial—both sides can be winners.